Primitive neuroectodermal tumour with synchronous ipsilateral clear cell carcinoma of the kidney. Issue 1 (9th December 2018) - Taha, Mohamed; Mohammed, Nur M; Crowther, Stephen; Manecksha, Rustom P; Thomas, Arun Z
Abstract : We report the first case of a synchronous ipsilateral primitive neuroectodermal tumour (PNET) and clear cell renal cell carcinoma of the kidney. A 37-year-old man presented to the emergency department with a 24-hour history of colicky abdominal pain and visible haematuria. He had no relevant surgical or medical history. Physical examination was unremarkable apart from mild left flank tenderness. Triphasic CT of the abdomen and pelvis showed two solid lesions in the left kidney. Further staging CT of the chest showed no evidence of local or distal metastasis. He subsequently underwent laparoscopic radical nephrectomy. Pathological analysis of the kidney showed two synchronous renal tumours, a clear cell carcinoma and PNET of the kidney. The patient received adjuvant chemotherapy according to Ewing's sarcoma chemotherapy protocol. Surveillance CT scans at 3, 6 and 12 months showed no evidence of disease recurrence or metastasis.